Training on Making Hand Washing Liquid Soap from Green Tea at PKK Mothers in Kranggan Village, Polanharjo, Klaten as an Effort to Improve Community Health and Economy - Aptika Oktaviana Trisna Dewi (Universitas Sahid Surakarta, 2024)
Abstract: Green tea is a plant that contains phytochemicals, namely polyphenols, alkaloids, volatile oils, polysaccharides, amino acids, lipids, and vitamin C. Flavonoids have antioxidant, anti-inflammatory, anti-allergic, and antibacterial activity. These advantages can be increased in terms of benefits and economic value by making it in the form of liquid soap. The addition of green tea is expected to increase the antioxidant effect of the soap preparations made. The study aims to provide training on making liquid hand-washing soap from steeping green tea leaves. The training activity for making liquid hand-washing soap with the addition of green tea was carried out as an effort to increase health independence and provide entrepreneurial provisions for the PKK community in Kranggan Village, Polanharjo, Klaten. The training was attended by 20 participants with presentation methods and practice in making liquid hand-washing soap. The result of this service activity is that the community knows how to make hand-washing soap from green tea and knows the function of the ingredients used in the process of making hand-washing soap. Keywords: training, devotion, liquid soap, green tea